AKULTURASI PADA MASA UMAYYAH DAN ABBASIYYAH: KAJIAN BUDAYA TERHADAP TULISAN DUDUNG ABDURRAHMAN - Fransisca, Malia; Ris’an Rusli; Amilda Sani; Sidik Fauji (An-Nas, 2024)
This article aims to give us an idea that cultural acculturation has been going on for a long time. The type used in this research is library research. The result of this study is that from the perspective of Dudung Abdurrahman, the pattern of multiculturalism in this classical period has three characteristics. First, the Muslim community in the classical period was based on Arabic and Islamic culture which grew while maintaining existing cultures and rooted in the al-'Ashabiyyah al-Qabaliyyah tradition. Second, the pattern of the Muslim community that developed in Arabism politics. Third, the pattern of multiculturalism is more clearly demonstrated by the role of non-Arab communities in the context of the development of Islamic culture and civilization, as developed by the Abbasid dynasty.